Binder composition for non-aqueous electrolyte of rechargeable lithium battery, negative electrode for non-aqueous electrolyte of rechargeable lithium battery, and method of preparing binder composition
Patent Information
- Application Number
- KR1020210064942
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-04
- Filing Date
- 2021-05-20
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2041-05-20
Smart Images

Figure R1020210064942_ABST
Abstract
Description
Technology Field
[0001] The invention relates to a binder composition for a non-aqueous electrolyte secondary battery, a negative electrode for a non-aqueous electrolyte secondary battery, a non-aqueous electrolyte secondary battery, and a method for manufacturing the binder composition. Background Technology
[0002] Non-aqueous electrolyte secondary batteries have a problem in that when temperatures drop, the resistance of the electrolyte or the resistance of the oxidation-reduction reaction at the electrode interface increases, leading to a decrease in battery output and lifespan characteristics.
[0003] In order to solve these problems, research is being conducted on binder compositions for non-aqueous electrolyte secondary batteries that can improve the lifespan characteristics of the battery at room temperature or low temperature and also reduce internal resistance, as described in WO2015 / 045522 and Japanese Patent Publication No. 2016-042408.
[0004] However, when manufacturing a negative electrode active material layer using a binder composition for a non-aqueous electrolyte secondary battery containing a styrene-acrylic acid ester-based polymer as described in the above patents, bubbles are generated when applying the slurry for the negative electrode active material layer to the negative electrode current collector, making it easy for coating defects to occur on the negative electrode, and the negative electrode active material layer is easy to peel off from the negative electrode current collector after the first charge.
[0005] In particular, in pouch batteries sealed with materials such as aluminum laminate film, external pressure or heat may be applied during the first (initial) charge to ensure stable film formation at the interface between the electrode and the electrolyte and to suppress battery distortion. Consequently, in pouch batteries, the problem of the negative electrode active material layer peeling off from the negative electrode current collector becomes more severe during the first charge. The problem to be solved
[0006] One embodiment provides a binder composition for a non-aqueous electrolyte secondary battery that can improve battery output at low temperatures and can realize a negative electrode active material layer that is easy to apply to a negative electrode current collector and easy to adhere to.
[0007] Another embodiment provides a negative electrode for a non-aqueous electrolyte secondary battery comprising the binder composition.
[0008] Another embodiment provides a non-aqueous electrolyte secondary battery comprising the above-mentioned cathode.
[0009] Another embodiment provides a method for manufacturing a binder composition for a non-aqueous electrolyte secondary battery. means of solving the problem
[0010] One embodiment provides a binder composition for a non-aqueous electrolyte secondary battery comprising a hydrophobic copolymer containing a unit derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, an unsaturated carboxylic acid alkyl ester monomer, a (meth)acrylic acid monomer, and an unsaturated carboxylic acid amide monomer, and a water-soluble copolymer containing a unit derived from a (meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer, wherein the hydrophobic copolymer is dispersed in an aqueous solution, and the dynamic surface tension at a lifetime of 5 seconds by the maximum bubble pressure method with a solid content of 3 weight% is 65 mN / m or more and 75 mN / m or less.
[0011] In one embodiment, the dynamic surface tension at a lifetime of 5 seconds by the maximum compressive pressure method of 3 weight% of the solid content of the binder composition for a non-aqueous electrolyte secondary battery may be 65 mN / m or more and 75 mN / m or less.
[0012] In the binder composition for a non-aqueous electrolyte secondary battery according to one embodiment, the content of the water-soluble copolymer may be 15% by weight or more and 45% by weight or less, and the content of the hydrophobic copolymer may be 55% by weight or more and 85% by weight or less.
[0013] In the above water-soluble copolymer, the content of the unit derived from the (meth)acrylic acid-based monomer is 35% by weight or more and 65% by weight or less, the content of the unit derived from the (meth)acrylonitrile monomer is 35% by weight or more and 65% by weight or less, and the content of the unit derived from an additional monomer capable of copolymerizing with the unit derived from the (meth)acrylic acid-based monomer and / or the unit derived from the (meth)acrylonitrile monomer may be 0% by weight or more and 20% by weight or less.
[0014] In one embodiment, the water-soluble monomer may include an ethylenically unsaturated monomer containing a sulfonic acid group.
[0015] The above sulfonic acid group-containing ethylenically unsaturated monomer may be at least one selected from the group consisting of sodium ethyl 2-sulfonic acid (meth)acrylic acid, sodium methacryloyloxypolyoxypropylene sulfate ester, and phenyl ether methacrylate sulfate ester salt.
[0016] The viscosity of an aqueous solution of 10% by weight of the solid content of the above water-soluble copolymer may be 500 mPa·s or more and 3000 mPa·s or less.
[0017] Another embodiment provides a negative electrode for a non-aqueous electrolyte secondary battery comprising the above-mentioned binder composition for a non-aqueous electrolyte secondary battery and a negative electrode active material.
[0018] The above cathode may further include a water-soluble polymer compound.
[0019] In one embodiment, the water-soluble polymer compound may be an alkali metal salt of carboxymethylcellulose.
[0020] Another embodiment provides a non-aqueous electrolyte secondary battery comprising the above-mentioned cathode.
[0021] Another embodiment provides a method for preparing a water-dispersible binder composition for a non-aqueous electrolyte secondary battery, comprising the step of synthesizing a hydrophobic copolymer comprising a unit derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, unsaturated carboxylic acid alkyl ester monomers, (meth)acrylic acid monomers, and unsaturated carboxylic acid amide monomers, in the presence of a water-soluble copolymer comprising a unit derived from a meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer. Effects of the invention
[0022] A binder composition for a non-aqueous electrolyte secondary battery according to one embodiment can significantly improve battery output at low temperatures, suppress bubble formation when applying a negative electrode active material layer composition to a current collector, and suppress the problem of the negative electrode active material peeling off from the negative electrode current collector during initial charging.
[0023] In addition, the binder composition for a non-aqueous electrolyte secondary battery according to one embodiment comprises a hydrophobic copolymer containing a unit derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, unsaturated carboxylic acid alkyl ester monomers, (meth)acrylic acid monomers, and unsaturated carboxylic acid amide monomers, and a water-soluble copolymer containing a unit derived from a (meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer, so that the battery output can be improved at low temperatures.
[0024] In addition, the binder composition for a non-aqueous electrolyte secondary battery according to one embodiment has a dynamic surface tension of 65 mN / m or more and 75 mN / m or less at a lifetime of 5 seconds by the maximum bubble pressure method with a solid content of 3 weight%, so it is possible to suppress the generation of bubbles when applying a negative electrode active material.
[0025] In addition, since the binder composition for a non-aqueous electrolyte secondary battery according to one embodiment includes the hydrophobic copolymer and the water-soluble copolymer, it is possible to suppress the delamination of the negative electrode active material from the negative electrode current collector during initial charging. Brief explanation of the drawing
[0026] FIG. 1 is a side cross-sectional view schematically showing the configuration of a lithium-ion secondary battery. Specific details for implementing the invention
[0027] Preferred embodiments of the present invention will be described in detail below with reference to the attached drawings. Meanwhile, in this specification and drawings, components having substantially the same functional configuration are given the same reference numerals so as to omit redundant descriptions.
[0028] <1. Non-aqueous electrolyte secondary battery>
[0029] A specific configuration of a non-aqueous electrolyte secondary battery according to one embodiment is described.
[0030] The lithium-ion secondary battery (1) shown in FIG. 1 is an example of a non-aqueous electrolyte secondary battery (1) according to one embodiment. As shown in FIG. 1, the lithium-ion secondary battery (1) includes a positive electrode (10), a negative electrode (20), a separator (30), and a non-aqueous electrolyte.
[0031] The charging voltage (oxidation-reduction potential) of the above lithium-ion secondary battery (1) is, for example, 4.0V (vs. Li / Li + ) or higher, 5.0V or lower, particularly 4.2V or higher, and 5.0V or lower.
[0032] The shape of the above lithium-ion secondary battery (1) is not particularly limited and may be any shape, such as, for example, cylindrical, prismatic, laminated, or button.
[0033] (1-1. Anode)
[0034] The positive electrode (10) may include a positive electrode current collector (11) and a positive electrode active material layer (12).
[0035] The above positive current collector (11) can be any conductive material, for example, plate-shaped or thin-shaped, and may be aluminum, stainless steel, nickel-coated steel, etc.
[0036] The above positive active material layer (12) may include at least a positive active material, and may additionally include a conductive agent and a positive binder.
[0037] The positive electrode active material is, for example, a transition metal oxide or solid solution oxide containing lithium, and is not particularly limited as long as it is a material capable of electrochemically absorbing and releasing lithium ions.
[0038] Transition metal oxides containing lithium include Li·Co-based complex oxides such as LiCoO2 and LiNi x Co y Mn z Examples of solid solution oxides include Li·Ni·Co·Mn-based complex oxides such as O2, Li·Ni-based complex oxides such as LiNiO2, or Li·Mn-based complex oxides such as LiMn2O4. As solid solution oxides, Li a MN x Co y Ni z O2(1.150≤a≤ 1.430, 0.45≤x≤ 0.6, 0.10≤y≤ 0.15, 0.20≤z≤ 0.28), LiMN 1.5 Ni 0.5 Examples include O4. Meanwhile, the content (content ratio) of the positive active material is not particularly limited and only an amount applicable to the positive active material layer (12) of the non-aqueous electrolyte secondary battery (1) is required. Additionally, these compounds may be used individually or mixed in multiples.
[0039] The conductive material is not particularly limited as long as it is intended to increase the conductivity of the anode (10). Specific examples of the conductive material include, for instance, one or more types selected from carbon black, natural graphite, artificial graphite, and fibrous carbon.
[0040] Examples of carbon black include furnace black, channel black, thermal black, ketjen black, and acetylene black.
[0041] Examples of fibrous carbon include carbon nanotubes, graphene, and carbon nanofibers.
[0042] The content of the conductive material is not particularly limited and may be an amount applicable to the positive active material layer (12) of the non-aqueous electrolyte secondary battery (1).
[0043] Examples of binders for the anode include fluorine-containing resins such as polyvinylidene fluoride, ethylene-containing resins such as styrene-butadiene rubber, ethylene-propylene-diene terpolymer, acrylonitrile-butadiene rubber, fluororubber, polyvinyl acetate, polymethyl methacrylate, polyethylene, polyvinyl alcohol, carboxymethyl cellulose or carboxymethyl cellulose derivatives (such as salts of carboxymethyl cellulose), or nitrocellulose. The positive binder is not particularly limited to any material that can bind the positive active material and the conductive material onto the positive current collector (11).
[0044] (1-2. Cathode)
[0045] The cathode (20) may include a cathode current collector (21) and a cathode active material layer (22). The cathode current collector (21) may be any conductive material, for example, plate-shaped or thin-shaped, and may include copper, stainless steel, nickel-plated steel, etc.
[0046] The negative electrode active material layer (22) comprises, for example, a binder composition for a non-aqueous electrolyte secondary battery, a negative electrode active material, and a water-soluble polymer compound.
[0047] The above-mentioned binder composition for a non-aqueous electrolyte secondary battery, together with the above-mentioned water-soluble polymer compound, binds the negative electrode active material layer (22) onto the negative electrode current collector (21).
[0048] In the negative electrode active material layer (22), the content of the binder composition for the non-aqueous electrolyte secondary battery may be, for example, 0.5 weight% or more and 3.5 weight% or less. If the content of the binder composition for the non-aqueous electrolyte secondary battery is 0.5 weight% or more, it is suitable to obtain a negative electrode (20) that makes it difficult for cracking or peeling of the negative electrode active material layer (22) to occur when the negative electrode active material layer (22) is coated, dried, and rolled. In addition, if the content of the binder composition for the non-aqueous electrolyte secondary battery is 3.5 weight% or less, it is suitable to obtain a negative electrode (20) with good cycle performance and without excessively increasing electrode resistance.
[0049] The negative electrode active material is not particularly limited as long as it is capable of electrochemically absorbing and releasing lithium ions, but examples include graphite active materials (synthetic graphite, natural graphite, a mixture of synthetic and natural graphite, natural graphite coated with synthetic graphite, etc.), Si-based active materials or Sn-based active materials (e.g., a mixture of graphite active materials and fine particles of silicon (Si), tin (Sn), or their oxides, fine particles of silicon or tin, alloys based on silicon or tin), metallic lithium, and Li4Ti5O. 12 Titanium oxide-based compounds, lithium nitride, etc., may be considered. As for the negative electrode active material, one type among the examples mentioned above may be used, or two or more types may be used in combination. Meanwhile, regarding silicon oxide, SiO₂ x It can be expressed as (0≤x≤2).
[0050] In the negative electrode active material layer (22) according to one embodiment, the content of the negative electrode active material may be 90 weight% or more and 99 weight% or less, and may be 94 weight% or more and 98 weight% or less.
[0051] If the content of the negative active material included in the negative active material layer (22) is 94 weight% or more, the electrode resistance does not increase excessively, and a negative electrode (20) with good cycle performance can be obtained. In addition, if the content of the negative active material included in the negative active material layer (22) is 98 weight% or less, a negative electrode (20) with better adhesion and good cycle performance can be obtained, which is suitable.
[0052] The above water-soluble polymer compound may be, for example, an alkali metal salt of carboxymethylcellulose.
[0053] In the negative electrode active material layer (22), the content of the water-soluble polymer compound may be, for example, 0.5 weight% or more and 2.5 weight% or less. If the content of the water-soluble polymer compound is 0.5 weight% or more, it is suitable for imparting good viscosity to the slurry for applying the negative electrode active material layer (22). On the other hand, if the content of the water-soluble polymer compound is 3.5 weight% or less, it is suitable for imparting excessive viscosity to the slurry for applying the negative electrode active material layer (22), so the slurry can be applied in a high solid content state and efficiently dried to obtain the negative electrode (20).
[0054] The coating amount of the negative active material layer (22) is 5 mg / cm² with an area density. 2 Above, 25 mg / cm² 2 It can be less than or equal to, and according to one embodiment, 10 mg / cm² 2 Above, 20 mg / cm² 2 It may be done below (based on single-sided coating).
[0055] In addition, the thickness of the negative active material layer (22) can be, for example, 50 μm or more and 150 μm or less as a cross-sectional thickness.
[0056] By setting the coating amount and thickness of the negative electrode active material layer (22) to the above range, the charge / discharge capacity of the non-aqueous electrolyte secondary battery can be further improved.
[0057] Meanwhile, the cathode (20) may further include a conductive agent. The conductive agent may be the one exemplified in the anode (10).
[0058] (1-3. Separator)
[0059] The separator (30) is not particularly limited and any material can be used as a separator (30) for a lithium-ion secondary battery (1). As the separator (30), a porous membrane or nonwoven fabric exhibiting excellent high-rate discharge performance can be used alone or in combination. The resin constituting the separator (30) may be, for example, a polyolefin-based resin represented by polyethylene, polypropylene, etc., a polyester-based resin represented by polyethylene terephthalate, polybutylene terephthalate, etc., polyvinylidene difluoride, vinylidene difluoride-hexafluoropropylene copolymer, vinylidene difluoride-perfluoroninylether copolymer, vinylidene difluoride-tetrafluoroethylene copolymer, vinylidene difluoride-trifluoroethylene copolymer, vinylidene difluoride-fluoroethylene copolymer. Copolymer (vinylidene difluoride-fluoroethylene copolymer), vinylidene difluoride-hexafluoroacetone copolymer, vinylidene difluoride-ethylene copolymer,Examples include vinylidene difluoride-propylene copolymer, vinylidene difluoride-trifluoropropylene copolymer, vinylidene difluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and vinylidene difluoride-ethylene-tetrafluoroethylene copolymer.
[0060] Meanwhile, the porosity of the separator (30) is not particularly limited, and it is possible to arbitrarily apply the porosity of the separator (30) of a conventional lithium-ion secondary battery (1).
[0061] The surface of the separator (30) may have a heat-resistant layer containing inorganic particles to improve heat resistance, or a layer containing an adhesive to fix the battery element by bonding to the electrode. Examples of the inorganic particles include Al2O3, AlOOH, Mg(OH)2, SiO2, etc. Examples of the adhesive include vinylidene fluoride-hexafluoropropylene copolymer, acid modified vinylidene fluoride polymer, styrene-(meth)acrylic acid ester copolymer, etc.
[0062] (1-4. Non-aqueous electrolyte)
[0063] The non-aqueous electrolyte can be any non-aqueous electrolyte that can be used in a conventional lithium-ion secondary battery (1) without any particular limitation. The non-aqueous electrolyte may have a composition containing an electrolyte salt in a non-aqueous solvent.Non-aqueous solvents include, for example, cyclic carbonate esters such as propylene carbonate, ethylene carbonate, butylene carbonate, chloroethylene carbonate, and vinylene carbonate; cyclic esters such as γ-butyrolactone and γ-valerolactone; chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethylmethyl carbonate; chain esters such as methylformate, methylacetate, methylbutyrate, ethyl propionate, and propylpropionate; tetrahydrofuran or its derivatives. 1,3-dioxane, 1,4-dioxane, 1,2-dimethoxyethane, 1,4-dibutoxyethane, or methyldiglyme, ethylene glycol monopropyl ether, propylene glycol monopropyl ether, ethers such as nitriles such as acetonitrile and benzonitrile, dioxolane or its derivatives, ethylene sulfide, sulfolane, sultone or its derivatives, etc., may be used alone or in a mixture of two or more.Meanwhile, when using a mixture of two or more solvents, the mixing ratio of each solvent can be applied as the mixing ratio used in a conventional lithium-ion secondary battery (1).
[0064] Examples of electrolytes include LiClO4, LiBF4, LiAsF6, LiPF6, and LIPF6. 6-x (C n F 2n+1 ) x (However, 1 <x <6, n=1 또는 2), LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10Inorganic ion salts containing one of lithium (Li), sodium (Na), or potassium (K), such as NaClO4, NaI, NaSCN, NaBr, KClO4, KSCN, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiC(C2F5SO2)3, (CH3)4NBF4, (CH3)4NBr, (C2H5)4NClO4, (C2H5)4NI, (C3H7)4NBr, (n-C4H9)4NClO4, (n-C4H9)4NI, (C2H5)4N-maleate, (C2H5)4N-benzoate, (C2H5)4N-phthalate, stearyl Examples include organic ionic salts such as lithium sulfonic acid (stearyl sulfonic acid lithium), lithium octyl sulfonic acid, and lithium dodecyl benzene sulfonic acid, and it is possible to use these ionic compounds alone or in a mixture of two or more types. Meanwhile, the concentration of the electrolyte salt may be the same as that of the non-aqueous electrolyte used in conventional lithium-ion secondary batteries (1), and there are no particular limitations. In one embodiment, it may be appropriate to use a non-aqueous electrolyte containing the lithium compound (electrolyte salt) described above at a concentration of 0.8 mol / l or more and 1.5 mol / l or less.
[0065] Meanwhile, various additives may be added to the non-aqueous electrolyte. Examples of such additives include cathodic additives, anode additives, ester-based additives, carbonate-based additives, sulfuric acid-based additives, phosphoric acid-based additives, boric acid-based additives, acid anhydride-based additives, and electrolyte-based additives. Any one of these may be added to the non-aqueous electrolyte, or multiple types of additives may be added to the non-aqueous electrolyte.
[0066] <2. Method for manufacturing a non-aqueous electrolyte secondary battery according to the present embodiment>
[0067] Next, a method for manufacturing a lithium-ion secondary battery (1) is described. The positive electrode (10) can be manufactured by the following method.
[0068] First, a mixture of a positive active material, a conductive material, and a positive binder in a desired ratio is dispersed in a solvent (e.g., N-methyl-2-pyrrolidone) to form a positive composite slurry. Subsequently, the positive composite slurry is applied over a positive current collector (11) and dried to form a positive active material layer (12). The application method is not particularly limited. Examples of application methods include a knife coater method, a gravure coater method, a reverse roll coater, a slit die coater, etc. Each of the following application processes can also be carried out in the same manner. Subsequently, the positive active material layer (12) is rolled to a desired density using a press machine. Accordingly, a positive electrode (10) is manufactured.
[0069] The cathode (20) is also manufactured in the same way as the anode (10). First, a mixture of materials constituting the cathode active material layer (22) is dispersed in a solvent (e.g., water) to produce a cathode composite slurry (hereinafter referred to as a slurry for a non-aqueous electrolyte battery cathode). Next, the cathode composite slurry is applied over a cathode current collector (21) and dried to form a cathode active material layer (22). Then, the cathode active material layer (22) is rolled with a press machine to achieve a desired density. Accordingly, the cathode (20) is manufactured.
[0070] Next, a separator (30) is positioned between the positive electrode (10) and the negative electrode (20) to manufacture an electrode structure. Next, the electrode structure is processed into a desired shape (e.g., cylindrical, prismatic, laminated, button-shaped, etc.) and inserted into a container of the shape. Next, a non-aqueous electrolyte is injected into the container so that the electrolyte impregnates each pore within the separator (30) or the pores of the positive electrode (10) and the negative electrode (20). Accordingly, a lithium-ion secondary battery (1) is manufactured.
[0071] <3. Binder composition according to the present embodiment>
[0072] The binder composition for a non-aqueous electrolyte secondary battery according to the present embodiment may include a hydrophobic copolymer and a water-soluble copolymer that disperses the hydrophobic copolymer in an aqueous solution. In addition, the binder composition may have a dynamic surface tension of 65 mN / m or more and 75 mN / m or less at a lifetime of 5 seconds using the maximum bubble pressure method of a water dispersion with a solid content of 3 weight%.
[0073] A binder composition according to one embodiment may have a core-shell structure in which a hydrophobic copolymer is coated with a water-soluble copolymer.
[0074] (3-1. Hydrophobic Copolymer)
[0075] The hydrophobic copolymer may include units derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, unsaturated carboxylic acid alkyl ester monomers, (meth)acrylic acid monomers, and unsaturated carboxylic acid amide monomers.
[0076] Examples of the above aromatic vinyl monomers include styrene, p-methylstyrene, m-methylstyrene, o-methylstyrene, o-butylstyrene, mt-butylstyrene, pt-butylstyrene, p-chlorostyrene, o-chlorostyrene, etc. According to one embodiment, the above aromatic vinyl monomer may be styrene.
[0077] Examples of the above unsaturated carboxylic acid alkyl ester monomers include (meth)acrylate methyl, (meth)acrylate ethyl, (meth)acrylate butyl, (meth)acrylate isopropyl, (meth)acrylate octyl, (meth)acrylate 2-ethylhexyl, (meth)acrylate isobutyl, (meth)acrylate pentyl, (meth)acrylate n-hexyl, (meth)acrylate isoamyl, (meth)acrylate lauryl, (meth)acrylate stearyl, (meth)acrylate isobornyl, etc.
[0078] Examples of the above (meth)acrylic acid-based monomers include methacrylic acid, acrylic acid, itaconic acid, fumaric acid, maleic acid, etc.
[0079] Examples of the above unsaturated carboxylic acid amide monomers include (meth)acrylamide, (meth)N-methylacrylamide, (meth)N-dimethylacrylamide, (meth)N-hydroxymethylacrylamide, (meth)N-butoxymethylacrylamide, (meth)isobutoxymethylacrylamide, etc.
[0080] The above hydrophobic copolymer may further include additional copolymerizable monomers. The above additional monomers include (meth)acrylate 2-hydroxyethyl, (meth)acrylate 2-hydroxypropyl, (meth)acrylate 2-hydroxybutyl, (meth)acrylate 2-hydroxy-3-phenoxypropyl, 2-acryloxyethyl-2-hydroxyethyl-phthalic acid, (meth)acrylate ethoxy-diethylene glycol, (meth)acrylate methoxy-triethylene glycol, (meth)acrylate tetrahydrofurfuryl, (meth)acrylate phenoxy-polyethylene glycol, (meth)acrylate phenoxydiethylene glycol, (meth)acrylate phenoxyethyl, (meth)acrylate methoxyethyl, (meth)acrylate glycidyl, (meth)acrylate (meth)acrylate (meth)acrylonitrile, Examples include 2-acrylamide-2-methylpropanesulfonic acid and 2-methacryloyloxyethylamide phosphate.
[0081] In a binder composition for a non-aqueous electrolyte secondary battery according to one embodiment, the content of the hydrophobic copolymer may be 55% by weight or more and 85% by weight or less.
[0082] If the content of the above hydrophobic copolymer is 55% by weight or more, the flexibility of the binder composition for a non-aqueous electrolyte secondary battery and the negative electrode active material layer (22) using the same can be further improved, and the occurrence of cracks during coating and drying in the air forming the negative electrode active material layer (22) can be suppressed, which is appropriate.
[0083] If the content of the above hydrophobic copolymer is 85 weight% or less, the content of the water-soluble copolymer in the binder composition can be 15 weight% or more. As a result, the storage stability of the cathode composite slurry can be further improved.
[0084] (3-2. Water-soluble copolymer)
[0085] The water-soluble copolymer may comprise units derived from (meth)acrylic acid monomers and units derived from (meth)acrylonitrile monomers. Additionally, the water-soluble copolymer may further comprise water-soluble monomers capable of copolymerizing with (meth)acrylic acid monomers and / or (meth)acrylonitrile.
[0086] In the above water-soluble copolymer, for example, the content of units derived from (meth)acrylic acid monomers may be 35 weight% or more and 65 weight% or less, the content of units derived from (meth)acrylonitrile monomers may be 35 weight% or more and 65 weight% or less, and the content of units derived from water-soluble monomers copolymerizable with (meth)acrylic acid monomers and / or (meth)acrylonitrile may be 0 weight% or more and 20 weight% or less.
[0087] If the content of units derived from the (meth)acrylic acid-based monomer in the water-soluble copolymer is 35 weight% or more, the water-soluble copolymer becomes easier to dissolve in water, thereby further improving the dispersibility of the cathode active material and the storage stability of the cathode composite slurry. In addition, if the content of units derived from the (meth)acrylic acid-based monomer is 65 weight% or less, the occurrence of cracks in the electrode during the coating and drying processes of the cathode composite slurry can be further suppressed, which is suitable.
[0088] In the water-soluble copolymer, if the content of the unit derived from (meth)acrylonitrile is 35 weight% or more, the adhesion of the negative electrode active material layer (22) to the negative electrode current collector (21) can be further improved, which is suitable. In addition, if the content of the unit derived from (meth)acrylonitrile in the water-soluble copolymer is 65 weight% or less, the water-soluble copolymer becomes easier to dissolve in water, which can further improve the dispersibility of the negative electrode active material or the storage stability of the negative electrode composite slurry, which is suitable.
[0089] If the content of units derived from (meth)acrylic acid-based monomers and (meth)acrylonitrile-copolymerizable water-soluble monomers in the water-soluble copolymer is 20% by weight or less, electrode cracking can be suppressed during the coating and drying process of the cathode composite slurry, or the delamination of the cathode active material from the cathode current collector (21) during the first charging.
[0090] The above (meth)acrylic acid-based monomer may include at least one selected from the group consisting of (meth)acrylic acid, metal salt of (meth)acrylic acid, ammonium salt of (meth)acrylic acid, and amine salt of (meth)acrylic acid.
[0091] The metal salt of the (meth)acrylic acid mentioned above may be, for example, an alkali metal salt of acrylic acid. Specific examples of the metal salt of the acrylic acid mentioned above include, for example, sodium acrylate, lithium acrylate, potassium acrylate, calcium acrylate, magnesium acrylate, sodium methacrylate, lithium methacrylate, potassium methacrylate, calcium methacrylate, etc. Among these, it is more appropriate to use sodium acrylate.
[0092] Examples of the ammonium salts of the above (meth)acrylic acid include the ammonia neutralized form of (meth)acrylic acid, the monoethanolamine neutralized form, the diethanolamine neutralized form, the hydroxylamine neutralized form, etc. Among these, it is more appropriate to use the ammonia neutralized form of acrylic acid.
[0093] In the water-soluble copolymer, the water-soluble monomer capable of copolymerizing with the (meth)acrylic acid-based monomer and (meth)acrylonitrile may include, for example, an ethylenically unsaturated monomer containing a sulfonic acid group.
[0094] Specific examples of the above sulfonic acid group-containing ethylenically unsaturated monomers include sodium ethyl (meth)acrylic acid 2-sulfonic acid, sodium methacryloyloxypolyoxypropylene sulfate ester, and phenyl ether methacrylate sulfate ester salt.
[0095] In one embodiment, if the water-soluble copolymer further includes, for example, an ethylenically unsaturated monomer containing a sulfonic acid group as such a water-soluble monomer, when preparing a binder composition for a non-aqueous electrolyte secondary battery, the ethylenically unsaturated monomer containing a sulfonic acid group functions as a reactive surfactant, so even if the content of the water-soluble copolymer is small, the polymerization reaction of the hydrophobic copolymer and the dispersion stability during storage can be improved, which is appropriate. Therefore, compared to the case where a reactive surfactant is not added, it is difficult to cause cracking or peeling of the negative electrode active material layer when the negative electrode active material layer is coated, dried, or rolled, which is appropriate.
[0096] To improve the dispersion stability of hydrophobic copolymers during polymerization and storage, non-reactive surfactants may be used. However, non-reactive surfactants tend to reduce surface tension, so the dynamic surface tension at a lifetime of 5 seconds using the maximum saturation pressure method of a water dispersion with a solid content of 3 wt% does not exceed 65 mN / m, making it unsuitable. Therefore, to achieve a dynamic surface tension of 65 mN / m or more, it is appropriate not to use non-reactive surfactants.
[0097] The viscosity of an aqueous solution of 10% by weight of the solid content of the above water-soluble copolymer may be in the range of 500 mPa·s or more and 3000 mPa·s or less.
[0098] If the viscosity of the water-soluble copolymer is 500 mPa·s or higher, it is suitable because it can further improve the adhesion of the negative electrode active material layer (22) to the negative electrode current collector (21). In addition, if the viscosity of the water-soluble copolymer is 3000 mPa·s or lower, it is suitable because it does not impart excessive viscosity to the slurry for applying the negative electrode active material layer (22), so the slurry can be applied in a high solid content state, the drying time can be reduced to improve productivity, and the negative electrode (20) can be obtained by drying efficiently.
[0099] There are no particular limitations on the manufacturing method for achieving the above viscosity, but the viscosity can be increased by using a divinyl monomer. As the above divinyl monomer, N,N′-methylenebisacrylamide, ethylene glycol methacrylate, N,N'-ethylenebis[2-(vinylsulfonyl)acetamido], N,N'-trimethylenebis[2-(vinylsulfonyl)acetamido], etc. can be used.
[0100] The content of the water-soluble copolymer in the binder composition for a non-aqueous electrolyte secondary battery may be 15% by weight or more and 45% by weight or less.
[0101] If the content of the above water-soluble copolymer is 15% by weight or more, the stability of the above hydrophobic copolymer during the polymerization reaction and storage can be further improved. In addition, if the content of the water-soluble copolymer is 45% by weight or less, it is difficult to cause cracking or peeling of the negative electrode active material layer (22) when the negative electrode active material layer (22) is coated, dried, and rolled, so it is suitable.
[0102] That is, a binder composition for a non-aqueous electrolyte secondary battery according to one embodiment comprises a hydrophobic copolymer comprising a unit derived from one or more monomers selected from the group consisting of an aromatic vinyl monomer, an unsaturated carboxylic acid alkyl ester monomer, a (meth)acrylic acid monomer, and an unsaturated carboxylic acid amide monomer, and a water-soluble copolymer comprising a unit derived from a (meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer, wherein the hydrophobic copolymer is dispersed in an aqueous solution. As the binder composition for a non-aqueous electrolyte secondary battery comprises the above composition, the battery output can be improved at low temperatures.
[0103] <4. Method for manufacturing a binder composition for a non-aqueous electrolyte secondary battery according to the present embodiment>
[0104] The binder composition for a non-aqueous electrolyte secondary battery according to the present embodiment can be manufactured, for example, by the following process or sequence.
[0105] (4-1. Synthesis of Water-Soluble Copolymers)
[0106] In a flask, an acrylic acid-based monomer, acrylonitrile, and, if necessary, other water-soluble polymerizable monomers are mixed. This mixing process may be carried out in an aqueous solution containing sodium hydroxide and / or ammonia, etc., if necessary. Afterward, the inside of the flask is replaced with nitrogen and heated to 50°C to 70°C. When the temperature of the solution reaches 50°C to 70°C, a reaction initiator is added and polymerization is initiated. By reacting while stirring, an aqueous solution of the water-soluble copolymer can be obtained.
[0107] The above acrylic acid-based monomer may be acrylic acid.
[0108] As the above water-soluble polymerizable monomer, a reactive surfactant of an ethylenically unsaturated monomer containing a sulfonic acid group may be further added as needed. The above ethylenically unsaturated monomer containing a sulfonic acid group comprises, for example, one or more selected from sodium ethyl 2-sulfonic acid (meth)acrylic acid, sodium methacryloyloxypolyoxypropylene sulfate ester, and phenyl ether methacrylate sulfate ester salt.
[0109] Using such a reactive surfactant as the above-mentioned water-soluble polymerizable monomer is suitable because it allows the hydrophobic copolymer to be stably dispersed in water even if the amount of water-soluble copolymer added during the synthesis of the hydrophobic copolymer described later or during the preservation of the binder for non-aqueous electrolyte secondary battery is further reduced.
[0110] In the above mixing process, a divinyl monomer may be further used as a viscosity modifier. As the divinyl monomer, N,N′-methylenebisacrylamide, ethylene glycol methacrylate, N,N'-ethylenebis[2-(vinylsulfonyl)acetamido], N,N'-trimethylenebis[2-(vinylsulfonyl)acetamido], etc. may be used.
[0111] In addition, the above mixing process can be carried out in a solvent, and water can be used as the solvent.
[0112] (4-2. Synthesis of Binder Composition for Non-Aqueous Electrolyte Secondary Batteries)
[0113] An aqueous solution of the water-soluble copolymer obtained by the above process and a monomer that serves as a raw material for the hydrophobic copolymer are placed in a flask, and then the flask is nitrogen-substituted and heated to 50°C to 70°C. When the temperature of the solution reaches 50°C to 70°C, a reaction initiator is added and polymerization is initiated. By carrying out the polymerization reaction while stirring in the presence of the water-soluble copolymer, a hydrophobic copolymer is synthesized in a state of stable dispersion in water, and an aqueous solution of a binder composition for a non-aqueous electrolyte secondary battery is obtained.
[0114] The above monomer may be one or more monomers selected from the group consisting of aromatic vinyl monomers, unsaturated carboxylic acid alkyl ester monomers, (meth)acrylic acid monomers, and unsaturated carboxylic acid amide monomers, and specific examples are as described above.
[0115] As reaction initiators for water-soluble copolymers and hydrophobic copolymers, for example, azo compounds such as α,α'-azobis(isobutyronitrile) and 2,2'-azobis(2-methyl-N-2-hydroxyethylpropionamide), persulfates such as ammonium persulfate and potassium persulfate may be used. These reaction initiators may also be used in the form of aqueous solutions dissolved in water.
[0116] <5. Effects of the present embodiment>
[0117] According to the binder composition for a non-aqueous electrolyte secondary battery configured as described above, it comprises a hydrophobic copolymer comprising a unit derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, unsaturated carboxylic acid alkyl ester monomers, (meth)acrylic acid monomers, and unsaturated carboxylic acid amide monomers, and a water-soluble copolymer comprising a unit derived from a (meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer, and in one embodiment, the water-soluble copolymer is included in the shell, thereby improving the battery output at low temperatures.
[0118] In addition, since the hydrophobic copolymer is synthesized in the presence of a water-soluble copolymer, it is not necessary to separately add a non-reactive surfactant when preparing a binder composition for a non-aqueous electrolyte secondary battery.
[0119] As a result, compared to when a non-reactive surfactant is added separately, the decrease in dynamic surface tension at a lifetime of 5 seconds can be suppressed by the maximum volatility method of a binder composition for non-aqueous electrolyte secondary batteries with a solid content of 3 wt%, for example, by the maximum volatility method of a water dispersion with a solid content of 3 wt%, and the dynamic surface tension can be maintained in a range of 65 mN / m or more and 75 mN / m or less.
[0120] Since the dynamic surface tension at a lifetime of 5 seconds can be maintained at 65 mN / m or more and 75 mN / m or less by the maximum bubble pressure method of a binder composition for a non-aqueous electrolyte secondary battery with a solid content of 3 weight%, for example, the maximum bubble pressure method of a water dispersion with a solid content of 3 weight%, bubble generation when applying a negative electrode active material can be suppressed.
[0121] The dynamic surface tension may be 70 mN / m or more and 73 mN / m or less, and according to another embodiment, may be 71.5 mN / m or more and 72.0 mN / m or less.
[0122] In addition, since the binder composition according to one embodiment includes a hydrophobic copolymer and a water-soluble copolymer of the composition described above, it can suppress the delamination of the negative active material layer (22) from the negative current collector (21) during the first charge. Compared to the case where a binder composition containing only a styrene-acrylic acid ester polymer is used, the binder composition according to one embodiment can effectively suppress the problem of the negative active material layer delaminating from the negative current collector during the first charge. This delamination suppression effect is not thought to be due to the fact that the adhesion strength to the current collector is not reduced even in the high-temperature electrolyte during the first charge, as the binder composition includes a water-soluble copolymer of the composition described above.
[0123] In addition, in a binder composition for a non-aqueous electrolyte secondary battery, the content of the water-soluble copolymer can be suppressed to 45 weight% or less, so cracking during the coating and drying of the negative electrode active material layer can be reduced compared to a binder composition consisting only of a water-soluble copolymer containing units derived from (meth)acrylic acid monomers and units derived from (meth)acrylonitrile monomers.
[0124] (Example)
[0125] The present invention will be described below in more detail than based on specific embodiments. However, the following embodiments are merely examples of the present invention, and the present invention is not limited to the following embodiments.
[0126] In this embodiment, binders for non-aqueous electrolyte secondary batteries of Examples 1 and 2 and Comparative Examples 1 and 2 were prepared, secondary batteries using these were manufactured, and the secondary batteries were evaluated. Each of the embodiments and comparative examples will be described below.
[0127] <Example 1>
[0128] (Synthesis of water-soluble copolymers)
[0129] 60.0 g of acrylic acid, 75.0 g of acrylonitrile, 15.0 g of ethyl sodium (meth)acrylate 2-sulfonate, 0.225 g of N,N′-methylenebisacrylamide, 166.52 ml of a 4 mol / l aqueous sodium hydroxide solution, and 653.26 g of ion-exchanged water were added to a 2000 ml separable flask equipped with a mechanical stirrer, a stirring rod, and a thermometer, and stirred at 450 rpm. After stirring, the system was nitrogen-exchanged, and the jacket temperature was set to 85°C to raise the temperature. When the temperature in the system reached 60°C, an aqueous initiator solution was added in which 3338 mg of 2,2'-azobis(2-methyl-N-2-hydroxyethylpropionamide) was dissolved in 30.0 g of ion-exchanged water.
[0130] At a jacket temperature set to 85°C, stirring was continued for 12 hours from the addition of the initiator to obtain a pale yellow aqueous solution. This pale yellow aqueous solution is an aqueous solution containing a water-soluble copolymer. The non-volatile component of the aqueous solution after the reaction was measured to be 15.2 wt%. Subsequently, the pale yellow aqueous solution was concentrated by heated vacuum distillation to remove unreacted monomers. Next, ammonia water and ion-exchanged water were added to adjust the solid content concentration and pH of the polymer aqueous solution, thereby obtaining an aqueous solution of a water-soluble copolymer with a solid content of 7 wt% and a pH of 7.5. 25°C, shear rate 100 s -1 The viscosity of the 7 wt% aqueous solution of the water-soluble copolymer in this case was 606 mPa·s. The measurement was taken using an Anton Pulsar MCR102 rheometer at a rotation speed of 100 rpm.
[0131] (Synthesis of binder composition for non-aqueous electrolyte secondary batteries)
[0132] In a 1000ml separable flask equipped with a mechanical stirrer, a stirring rod, and a thermometer, 321.43g of an aqueous solution of the water-soluble copolymer with a solid content of 7 wt% and a pH of 7.5, 26.25g of styrene and 26.25g of 2-ethylhexyl acrylic acid, which are raw materials for the hydrophobic copolymer, and 121.07g of ion-exchanged water were injected and stirred at 550 rpm. After stirring, the system was nitrogen-exchanged, the jacket temperature was set to 70°C, and the temperature was raised. When the system temperature reached 60°C, an aqueous initiator solution prepared by dissolving 489mg of ammonium persulfate in 5.0g of ion-exchanged water was added. With the jacket temperature set to 70°C, stirring was continued for 12 hours following the addition of the initiator, and a milky white dispersion was obtained.
[0133] The above milky white dispersion is a liquid containing a binder composition for a non-aqueous electrolyte secondary battery. This liquid is formed by coating a hydrophobic copolymer, produced by copolymerizing styrene and 2-ethylhexyl acrylic acid added as raw materials for the hydrophobic copolymer, with a water-soluble copolymer, thereby stably dispersing the binder composition for a non-aqueous electrolyte secondary battery in water. The non-volatile component of the aqueous solution after the reaction was measured to be 15.0 wt%. Subsequently, the aforementioned milky white dispersion was concentrated by heated vacuum distillation to remove unreacted monomers. Next, ammonia water and ion-exchanged water were added, and the solid content concentration and pH were adjusted to obtain a dispersion of the binder composition for a non-aqueous electrolyte secondary battery with a pH of 7.5 containing 10 wt% solid content. 25°C, shear rate 100s -1 The viscosity of the dispersion with a solid content of 10 wt% in this case was 355 mPa·s.
[0134] <Example 2>
[0135] (Synthesis of binder composition for non-aqueous electrolyte secondary batteries)
[0136] 357.14 g of the aqueous solution of a water-soluble copolymer with a solid content of 7 wt% and a pH of 7.5 prepared in Example 1, 18.75 g of styrene and 18.75 g of 2-ethylhexyl acrylic acid, which are raw materials for the hydrophobic copolymer, and 100.36 g of ion-exchanged water were injected into a 1000 ml separable flask equipped with a mechanical stirrer, a stirring rod, and a thermometer, and stirred at 550 rpm. After stirring, the system was nitrogen-exchanged, and the temperature was raised by setting the jacket temperature to 70°C. When the temperature inside the system reached 60°C, an aqueous initiator solution prepared by dissolving 408 mg of ammonium persulfate in 5.0 g of ion-exchanged water was added.
[0137] At a jacket temperature of 70°C, stirring was continued for 12 hours with the addition of an initiator, and a milky white dispersion was obtained. This milky white dispersion is a liquid containing a binder composition for a non-aqueous electrolyte secondary battery. This liquid is a hydrophobic copolymer produced by copolymerizing styrene and 2-ethylhexyl acrylate, which were added as raw materials for the hydrophobic copolymer, and is coated by a water-soluble copolymer, resulting in a state where the binder composition for a non-aqueous electrolyte secondary battery is stably dispersed in water. The non-volatile component of the aqueous solution after the reaction was measured to be 12.5 wt%. Subsequently, the aforementioned milky white dispersion was concentrated by heated vacuum distillation to remove unreacted monomers. Afterward, ammonia water and ion-exchanged water were added, and the solid content concentration and pH were adjusted to obtain a dispersion of a binder composition for a non-aqueous electrolyte secondary battery with a pH of 7.5 containing 10 weight% of solid content. 25℃, shear rate 100s -1 The viscosity of the dispersion of a binder composition for a non-aqueous electrolyte secondary battery with a solid content of 10 wt% was 398 mPa·s.
[0138] <Comparative Example 1>
[0139] (Synthesis of binder composition for non-aqueous electrolyte secondary batteries)
[0140] 0.45 g of sodium dodecylbenzenesulfonate, a non-reactive (low molecular weight) surfactant, 18.75 g of styrene and 18.75 g of 2-ethylhexyl acrylic acid, which are raw materials for a hydrophobic copolymer, and 100.36 g of ion-exchanged water were injected into a 1000 ml separable flask equipped with a mechanical stirrer, a stirring rod, and a thermometer, and stirred at 550 rpm. After stirring, the system was nitrogen-exchanged, and the temperature was raised by setting the jacket temperature to 70°C. When the system temperature reached 60°C, an aqueous initiator solution was added in which 408 mg of ammonium persulfate was dissolved in 5.0 g of ion-exchanged water. With the jacket temperature set to 70°C, stirring was continued for 12 hours after the addition of the initiator, and a milky white dispersion was obtained. This milky white dispersion is a liquid containing a binder composition for a non-aqueous electrolyte secondary battery. This liquid consists of a hydrophobic copolymer coated with sodium dodecylbenzenesulfonate, a non-reactive surfactant, and dispersed in water. The non-volatile component of the aqueous solution after the reaction was measured to be 26.0 wt%. Subsequently, the aforementioned milky white dispersion was concentrated by heated vacuum distillation to remove unreacted monomers. Afterward, ammonia water and an ion-exchange water were added, and the solid content and pH were adjusted to obtain a binder composition dispersion for a non-aqueous electrolyte secondary battery with a pH of 7.5 containing 10 wt% solids. 25°C, shear rate 100 s -1 The viscosity of the dispersion liquid of the binder composition for secondary batteries with a solid content of 10 mass% in the non-aqueous electrolyte was 398 mPa·s.
[0141] <Comparative Example 2>
[0142] As a binder composition for a non-aqueous electrolyte secondary battery, commercially available modified styrene butadiene rubber (hereinafter referred to as modified SBR) was used.
[0143] Measurement of Dynamic Surface Tension
[0144] The dynamic surface tension of a binder composition for a non-aqueous electrolyte secondary battery prepared with a solid content of 3 wt% was measured by measuring the change over time using the maximum pressure method with a dynamic surface tension meter BP-D5L manufactured by Kwahyup Intermediate Science Co., Ltd., and the value at a lifetime of 5000 msec was taken as the dynamic surface tension. The results are shown in Table 1 below.
[0145] Dynamic surface tension (Mn / m) Example 1 71.5 Example 2 72.0 Comparative Example 1 62.0 Comparative Example 2 70.5
[0146] <Cathode Coating Evaluation>
[0147] (Cathode fabrication)
[0148] A negative electrode composite slurry was prepared by dissolving and dispersing graphite, a binder composition for non-aqueous electrolyte secondary batteries, and a sodium salt of carboxymethylcellulose in a water solvent at a solid-to-mass ratio of 97.5:1.5:1. Subsequently, this negative electrode composite slurry was applied to both sides of a 10 μm thick copper foil current collector and dried. A double-sided negative electrode was manufactured by rolling the coating layer after drying. The density of the negative electrode active material layer after rolling was 1.65 g / cm³. 3 It was, and the application amount was 11 mg / cm² on each side. 2 It was.
[0149] (Cathode Coating Evaluation)
[0150] For the double-sided cathode manufactured and rolled by the above process, the number of grooves thought to be coating defects caused by bubble formation within 5 randomly selected 15 cm squares was counted. The results are shown in Table 2.
[0151] Number of indentations (average / per side) Example 1 0.0 Example 2 0.0 Comparative Example 1 2.5 Comparative Example 2 0.0
[0152] <Evaluation of peeling during first charge>
[0153] (Production of the bipolar system)
[0154] A cathode composite slurry was prepared by dissolving and dispersing lithium cobalt oxide, carbon black, and polyvinylidene fluoride (PVDF) in N-methylpyrrolidone at a solid weight ratio of 97.5:1.2:1.3. The above cathode composite slurry was applied to one side of an aluminum foil current collector with a thickness of 12 μm and dried. The coated layer after drying was rolled to produce a cathode with a cathode active material layer formed on one side. The density of the cathode active material layer after rolling was 4.15 g / cm³. 3 was, and the application amount was 19.5 mg / cm² 2 It was.
[0155] (Fabrication of non-aqueous electrolyte secondary batteries)
[0156] After welding aluminum and nickel lead wires to the single-sided anode and double-sided cathode manufactured by the above process, the single-sided anode was folded in half so that the anode active material layer was on the inside, and a polyethylene porous separator was folded in half and placed on the inside of the folded anode.
[0157] Two-sided cathodes were placed further inside the separator, and the positive and negative electrodes were positioned opposite each other with the separator interposed, and these were housed in an aluminum laminate film with lead wires drawn out to the outside.
[0158] Here, a secondary battery was manufactured by injecting an electrolyte and sealing under reduced pressure. As the electrolyte, 1M LiPF6 was dissolved in a solvent mixed with ethylene carbonate and ethyl propionate in a volume ratio of 3:7.
[0159] (Delamination evaluation during first charge)
[0160] After injecting the electrolyte, the secondary battery was left at 25°C for 12 hours and placed between two 500 µm porous polytetrafluoroethylene (PTFE) sheets. In this state, a pressure of 0.8 MPa was applied using a heat press set to 60°C, and constant current charging was performed up to 4.4 V at 1 / 5 CA of the design capacity (1 CA is a 1-hour discharge rate), followed by constant voltage charging at 4.4 V until it reached 1 / 20 CA. Afterward, the battery was cooled to room temperature to release the pressure, the secondary battery was disassembled in a glove box, and the condition of the negative electrode was observed visually. The results are shown in Table 3.
[0161] cathode state Example 1 No peeling Example 2 No peeling Comparative Example 1 peeling Comparative Example 2 No peeling
[0162] <Low-temperature output evaluation>
[0163] After injecting the liquid, the secondary battery was placed between two 500 μm porous PTFE sheets after being left at 25°C for 12 hours, and while applying a pressure of 0.8 MPa using a heat press set to 60°C, constant current charging was performed up to 4.4V at 1 / 5 CA of the design capacity (1 CA is a 1-hour discharge rate), and constant voltage charging was continued at 4.4V until it reached 1 / 20 CA. Subsequently, the pressure was released by cooling to room temperature, and the battery was placed between two bakelite plates and constant current discharge was performed at 25°C at 1 / 5 CA down to 3.0V. After that, constant current charging up to 4.4V at 1 / 5 CA of the design capacity, constant voltage charging up to 1 / 20 CA at 4.4V, and constant current discharge down to 3.0V at 1 / 2 CA were repeated three times. In addition, constant current charging was performed at 1 / 5 CA to 4.4 V, and constant voltage charging was performed at 4.4 V until it reached 1 / 20 CA. Afterward, the secondary battery was transferred to a -10°C constant temperature bath and left idle for 3 hours to cool down to the same temperature as the set temperature. After that, constant current discharge was performed at 1 / 2 CA to 3.0 V.
[0164] The discharge capacity at this time was divided by the discharge capacity of the third 1 / 2CA discharge performed at 25℃ to calculate the discharge capacity retention rate of -10℃ relative to 25℃. The results are shown in Table 4.
[0165] Cold capacity retention rate (%) Example 1 74 Example 2 73 Comparative Example 1 73 Comparative Example 2 68
[0166] (Consideration)
[0167] As shown in Tables 1 and 2, when the dynamic surface tension of a binder composition for a non-aqueous electrolyte secondary battery prepared with 3 wt% solid content is measured, it can be seen that if the value at a lifetime of 5000 msec is 65 mN / m or more and 75 mN / m or less, it is difficult for bubbles to form when the negative electrode active material layer is applied, and the formation of grooves considered to be coating defects on the negative electrode can be suppressed.
[0168] In addition, as shown in the results of Table 3, it can be seen that using the binder compositions for non-aqueous electrolyte secondary batteries of Examples 1 and 2 can suppress the delamination of the negative active material layer from the negative current collector during the first charge.
[0169] As can be seen from the results in Table 4, the battery output at low temperatures could be improved compared to when using modified styrene-butadiene rubber (SBR), which is a conventional binder composition for non-aqueous electrolyte secondary batteries. Regarding the modified SBR of Comparative Example 2, it was confirmed that the same results as in Table 4 were obtained even when testing various different types of materials.
[0170] Integrating the above results, it can be seen that using a binder composition for a non-aqueous electrolyte secondary battery according to one embodiment improves battery output at low temperatures, suppresses delamination of the negative electrode active material from the negative electrode current collector, and suppresses coating defects of the negative electrode caused by bubble generation during the coating of the negative electrode active material.
[0171] In each of the above-described embodiments, ethyl sodium methacrylate, which functions as a reactive surfactant, was used as a raw material for the water-soluble polymer, but such a reactive surfactant is not strictly necessary. For example, even if the content of the water-soluble copolymer in the binder composition for a non-water electrolyte secondary battery is 40% by weight or more, the value at the lifetime of 5000 msec of the binder composition for a non-water electrolyte secondary battery can be maintained in the range of 65 mN / m or more and 75 mN / m or less.
[0172] When measuring the dynamic surface tension of a binder composition for a non-aqueous electrolyte secondary battery, if the value at a lifetime of 5000 msec is 65 mN / m or more and 75 mN / m or less, it is difficult for bubbles to form when the negative electrode active material layer is coated, and the formation of grooves considered to be coating defects on the negative electrode can be suppressed. This is related to the surface tension during the time from when the negative electrode composite slurry is coated until it is dried and fixed. It is thought that if the surface tension of the coated surface is high during this time, the generated bubbles cannot be stabilized and are quickly defoamed, resulting in a good coating surface, whereas if the interface is stabilized, the generated bubbles do not disappear and are dried as is, resulting in defects on the dried coating surface.
[0173] As described above, the binder composition for a non-aqueous electrolyte secondary battery according to one embodiment is a water-dispersed type in which a hydrophobic copolymer is stably dispersed in an aqueous solution by a water-soluble copolymer. It is believed that this binder composition for a non-aqueous electrolyte secondary battery enables the hydrophobic copolymer to be stably dispersed in water by positioning the water-soluble copolymer on the surface of the hydrophobic copolymer.
[0174] In addition, cases where hydrophobic copolymers and hydrophilic copolymers are not separated even after centrifugation, and where at least a portion of the hydrophobic copolymers and hydrophilic copolymers are bonded to each other through some chemical interaction, are considered. Explanation of the symbols
[0175] 1… Lithium-ion secondary battery 10… bipolar 20… cathode 30… Separator
Claims
Claim 1 A binder composition for a non-aqueous electrolyte secondary battery comprising: a hydrophobic copolymer comprising a unit derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, unsaturated carboxylic acid alkyl ester monomers, (meth)acrylic acid monomers, and unsaturated carboxylic acid amide monomers; and a water-soluble copolymer comprising a unit derived from a (meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer, wherein the hydrophobic copolymer is dispersed in an aqueous solution, and wherein the dynamic surface tension at a lifetime of 5 seconds by the maximum bubble pressure method with a solid content of 3 weight% is 65 mN / m or more and 75 mN / m or less, wherein the binder composition has a core-shell structure in which the hydrophobic copolymer is coated with the water-soluble copolymer. Claim 2 A binder composition for a non-aqueous electrolyte secondary battery according to claim 1, wherein the dynamic surface tension is 70 mN / m or more and 73 mN / m or less. Claim 3 A binder composition for a non-aqueous electrolyte secondary battery according to claim 1, wherein the content of the water-soluble copolymer is 15% by weight or more and 45% by weight or less, and the content of the hydrophobic copolymer is 55% by weight or more and 85% by weight or less. Claim 4 A binder composition for a non-aqueous electrolyte secondary battery according to claim 1, wherein the water-soluble copolymer comprises 35% by weight or more and 65% by weight or less of a unit derived from the (meth)acrylic acid-based monomer, 35% by weight or more and 65% by weight or less of a unit derived from the (meth)acrylonitrile monomer, and further comprises 0% by weight or more and 20% by weight or less of a unit derived from a water-soluble monomer capable of copolymerizing with the unit derived from the (meth)acrylic acid-based monomer and / or the unit derived from the (meth)acrylonitrile monomer. Claim 5 A binder composition for a non-aqueous electrolyte secondary battery according to claim 4, wherein the water-soluble monomer comprises an ethylenically unsaturated monomer containing a sulfonic acid group. Claim 6 A binder composition for a non-aqueous electrolyte secondary battery according to claim 5, wherein the sulfonic acid group-containing ethylenically unsaturated monomer is at least one selected from the group consisting of (meth)acrylic acid 2-sulfonic acid ethyl sodium, methacryloyloxypolyoxypropylene sulfate ester sodium, and phenyl ether methacrylate sulfate ester salt. Claim 7 In claim 1, the viscosity of an aqueous solution having a solid content of 7 weight% of the water-soluble copolymer is 500 mPa·s or more and 3000 mPa·s or less, and the viscosity is at 25°C and a shear rate of 100s -1 A binder composition for a non-aqueous electrolyte secondary battery, the value measured at a rotational speed of 100 rpm using an Anton Pulsar rheometer MCR102. Claim 8 A binder composition for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 7; and a negative electrode for a non-aqueous electrolyte secondary battery comprising a negative electrode active material. Claim 9 In claim 8, the cathode is a cathode for a non-aqueous electrolyte secondary battery that further comprises a water-soluble polymer compound. Claim 10 In claim 9, the above-mentioned water-soluble polymer compound is an alkali metal salt of carboxymethylcellulose, a negative electrode for a non-aqueous electrolyte secondary battery. Claim 11 A non-aqueous electrolyte secondary battery comprising the negative electrode of claim 8. Claim 12 A method for preparing a binder composition for a water-dispersible non-aqueous electrolyte secondary battery, comprising the step of synthesizing a hydrophobic copolymer comprising a unit derived from one or more monomers selected from the group consisting of aromatic vinyl monomers, unsaturated carboxylic acid alkyl ester monomers, (meth)acrylic acid monomers, and unsaturated carboxylic acid amide monomers in the presence of a water-soluble copolymer comprising a unit derived from a (meth)acrylic acid monomer and a unit derived from a (meth)acrylonitrile monomer, wherein the hydrophobic copolymer has a core-shell structure coated with the water-soluble copolymer.
Citation Information
Patent Citations
Lithium ion secondary battery positive electrode
JP2019133908A
Binder aqueous solution for lithium ion battery, slurry for lithium ion battery electrode and manufacturing method therefor, lithium ion battery electrode, and lithium ion battery
JP2020043064A
Binder composition for secondary-battery electrode, slurry composition for secondary-battery electrode, secondary-battery electrode, and secondary battery
KR1020170053615A
